2015
DOI: 10.1016/j.ajpath.2015.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Functional Glycosylation of α-Dystroglycan in FKRP Mutant Mice Is Associated with Muscle Regeneration

Abstract: Mutations in fukutin-related protein (FKRP) gene are characterized with lack of functionally glycosylated α-dystroglycan (F-α-DG). Surprisingly, a few muscle fibers express strong F-α-DG. Herein, we investigated the restoration of F-α-DG in the FKRP mutant muscles and showed that the restoration of glycosylation is associated with muscle regeneration and dependent on the expression of both like-glycosyltransferase (LARGE) and partially functional FKRP. F-α-DG in the regenerating fibers reaches up to normal lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 65 publications
3
31
0
Order By: Relevance
“…59 IIH6 also can block laminin binding to the O-mannosephosphateelinked glycans present on the a dystroglycan protein. 7 Consistent with the findings reported by Lu and colleagues, 60 we observed IIH6 expression predominantly Figure 5 Quantification of immunoglobulin G (IgG) uptake after overexpression of GALGT2 in FKRP P448Lneo À mice. The gastroc, quad, and TA muscles of FKRP P448Lneo À mutant mice were injected with rAAVrh74.MCK.GALGT2 (treated) or PBS (untreated) and compared at 1, 3, and 6 months after injection.…”
Section: Effect Of Raavrh74mckgalgt2 Treatment On a Dystroglycan Exsupporting
confidence: 88%
“…59 IIH6 also can block laminin binding to the O-mannosephosphateelinked glycans present on the a dystroglycan protein. 7 Consistent with the findings reported by Lu and colleagues, 60 we observed IIH6 expression predominantly Figure 5 Quantification of immunoglobulin G (IgG) uptake after overexpression of GALGT2 in FKRP P448Lneo À mice. The gastroc, quad, and TA muscles of FKRP P448Lneo À mutant mice were injected with rAAVrh74.MCK.GALGT2 (treated) or PBS (untreated) and compared at 1, 3, and 6 months after injection.…”
Section: Effect Of Raavrh74mckgalgt2 Treatment On a Dystroglycan Exsupporting
confidence: 88%
“…We also noticed strongly reduced expression levels of glycosylated α-dystroglycan protein using monoclonal antibody IIH6C4 ( Figure 1E). These results are consistent with previous findings in our FKRP-morphant zebrafish and in the Fkrp (P448L) severe mouse model (23,24). Likewise, we observed significant decreases in overall laminin expression ( Figure 1E), a hallmark of FKRP-dependent dystroglycanopathies, as also observed in whole-brain protein lysates of Fkrp Y307N-mutant mice (15).…”
Section: Resultssupporting
confidence: 93%
“…Recent work in gene therapy has shown that overexpression of full-length FKRP protein using systemic AAV delivery can block muscle wasting and cardiac symptoms associated with LGMD2I (33,46). Additionally, AAV-mediated FKRP overexpression is capable of restoring the expression levels and complexity of α-dystroglycan glycosylation in FKRP-mutant mice (24). Nevertheless, a comprehensive functional role of FKRP in skeletal muscle along with other tissues remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, genetic and biochemical analyses of FKRP-related dystroglycanopathies indicated that residual glycosylation is present in patients as well as in the muscles of our FKRP P448L mutant model. 6,26 Therefore, we investigated whether purified recombinant chick mAgrin could enhance the binding of the residual glycosylated a-DG or the hypoglycosylated a-DG to laminin(s) or other extracellular matrix proteins. We examined such potential effects in vitro using cultured myoblasts and fibroblasts from both the FKRP P448L mutant and normal C57BL/6 mice ( Figure 1).…”
Section: Expression Of Magrin In Vitro Enhances Laminin Bindingmentioning
confidence: 99%